Intertextual in The Novel Titik Nol by Augustine Wibowo with The Novel Ibuk by Iwan Setyawan - Yuliarti, Yuliarti; Nastiti, Ana Putri (J-LELC: Journal of Language Education, Linguistics, and Culture, 2024)
This research investigates the intertextual aspects in two novels, namely "Titik Nol" by Wibowo and "Ibuk" by Setyawan. The aim of this study is to compare the intertextual relationships between themes, events, and characters in both novels. The research method employed is a qualitative approach and descriptive method to illustrate the intertextual relationships between them. The findings of this research serve as documentation of the intertextual relationships in "Titik Nol" and "Ibuk," obtained through documentation techniques and literature review. This study suggests the importance of understanding the intertextual relationships among literary works in analyzing themes, events, and characters. The finding that both novels share similar main themes provides deep insights into narratives that may be related to specific social, cultural, or historical contexts. Emphasizing the similarities and differences in events and characters highlights the complexity of interpretation and narrative formation in literature. Documentation of these intertextual relationships also provides a foundation for further research in understanding the influence and evolution of themes and narrative characteristics in literature.